2015
DOI: 10.1519/jsc.0000000000000917
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength, Power, and Morphologic Adaptations After 6 Weeks of Compound vs. Complex Training in Healthy Men

Abstract: The aim of the study was to compare the effects of compound vs. complex resistance training on strength, high-speed movement performance, and muscle composition. Eighteen young men completed compound (strength and power sessions on alternate days) or complex training (strength and power sets within a single session) 3 times per week for 6 weeks using bench press, leg press, Smith machine box squat, and jumping exercises. Pre- and posttraining, jumping and throwing performance and maximum bench press, leg press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 25 publications
(12 reference statements)
6
63
2
3
Order By: Relevance
“…Overall, training-induced increases in fascicle length are accompanied by an increase in muscle size (muscle hypertrophy, which is defined as an increase in muscle fiber area, muscle thickness, anatomical crosssectional area or volume in this article), although four studies failed to find muscle hypertrophy 45,52,54,55) and two studies did not show the data on muscle size 56,57) . Two studies observed a decrease in fascicle length of the gastrocnemius with 58) and without 59) muscle hypertrophy, and Timmins et al 55) showed a decrease in the fascicle length of BF without muscle hypertrophy. It should be noted that some reports 43,45) calculated fascicle length as the muscle thickness divided by the sine component of the pennation angle determined by small probe width, which could involve a large error 14) .…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 98%
See 1 more Smart Citation
“…Overall, training-induced increases in fascicle length are accompanied by an increase in muscle size (muscle hypertrophy, which is defined as an increase in muscle fiber area, muscle thickness, anatomical crosssectional area or volume in this article), although four studies failed to find muscle hypertrophy 45,52,54,55) and two studies did not show the data on muscle size 56,57) . Two studies observed a decrease in fascicle length of the gastrocnemius with 58) and without 59) muscle hypertrophy, and Timmins et al 55) showed a decrease in the fascicle length of BF without muscle hypertrophy. It should be noted that some reports 43,45) calculated fascicle length as the muscle thickness divided by the sine component of the pennation angle determined by small probe width, which could involve a large error 14) .…”
Section: Longitudinal Study Evidence For Fascicle Length Changementioning
confidence: 98%
“…These studies strongly suggest that a generic hypertrophic process in a pennate muscle is accompanied by an increase in pennation angle. On the other hand, an increase in pennation angle of the gastrocnemius without hypertrophy was indicated after marathon training 59) and complex training (strength and power sets within a single session) 58) or of BF after concentric-only training 55) . These results cannot be explained by the strategy mentioned above.…”
Section: Evidence For Pennation Angle Changementioning
confidence: 99%
“…Images were analysed for muscle thickness, fascicle angle, and fascicle length with image analysis software (Motic Images Plus 2.0, Motic, Hong Kong, China). Muscle thickness was defined as the mean of the distances between the superficial and deep aponeurosis measured at the ends of each panoramic image [26,27] …”
Section: Muscle Architecturementioning
confidence: 99%
“…Fascicle length is thought to reflect the number of sarcomeres in series in a muscle and the increase in this number has been suggested to contribute to higher shortening velocity and muscle power [19]. Longer fascicles are typically found in agonist muscles of faster sprinters [20][21][22], while studies in humans have reported longitudinal muscle growth in response to power training [23][24][25][26][27]. Recently, a correlation was found between vastus lateralis fascicle length and late RFD (100-250 ms) in young aged track and field throwers [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Each of the aforementioned aspects of muscle structure can be reliably 2 and noninvasively quantified for multiple upper and lower body muscles via ultrasonography. This notion has led to muscle structure assessments forming part of a range of recently conducted cross-sectional [3][4][5][6][7] and intervention studies [8][9][10][11] . Correlational analyses conducted as part of many of these studies have linked distinct aspects of lower body muscle architecture to peak force and power measured during several dynamic 3,4,7 and isometric 3,8 tasks thought to be beneficial to athletic performance.…”
Section: Introductionmentioning
confidence: 99%